3D Photonic Crystals for Direct Applications in Light Emitting Devices - Matej Goraus; Petra Urbancova; Dusan Pudis (Advances in Electrical and Electronic Engineering, 2018)
In this paper, we present IP-Dip polymer-based Photonic Crystals (PhCs), which are more and more attractive for photonic devices. These structures offer simple and cheap solutions, how to improve optical properties of these devices. In our experiment, we used Direct Laser Writing (DLW) lithography to create a three dimensional (3D) PhCs. We fabricated two types of PhC structure. The first structure was prepared from IP-Dip polymer and used for modification of the radiation pattern of the optical fiber. The second PhC structure was filled with liquid polymer PolyDiMethylSiloxane (PDMS) and directly placed on the LED chip. Quality of the prepared structures was confirmed by a confocal microscope. The modification of the far-field radiation patterns of LED and optical fiber was measured by a goniophotometer.